Solusi Mengatasi Sikap Putus Asa: Pendekatan Tafsir Al-Azhar dalam Perspektif Spiritual dan Sosial - Shofia Anahdiah; Achmad Khudori Soleh (MADINAH, 2024)
Hopelessness is considered an attitude that is prohibited by Islamic teachings, because Allah Swt. always provides a way out with the best solutions for his servants. One of the basic sources of Islamic teachings that provides solutions is theQuran. Therefore, this research aims to know and understand how to overcome despair. This study examines the relevant verses of the Quran, with the problem of despair and its solution. The Quran and thebook of tafsir byBuya Hamka with thetitle Al Azhar as the first reference material, using the descriptive qualitative content analysis method. Solutions explained in the Quran are explored to overcome the attitude of despair. The results of this study highlight a number of issues, chief among them being (1) the reference of hopelessness in the Koran, where the term "ya'isa" is used thirteen times in nine surahs in distinct contexts. Ya'isa occurs twice, Ya'isu appears three times, and Istaiasa appears once. Furthermore, there are single mentions of istaiasu, ya'iasu, taiasu, ya'uusun, ya'uusan, ya'isna, and yai'asi. (2) Allah Swt. forbids mankind to have a desperate attitude as stated in the Quran surah Az Zumar verse 53 and QS. The prohibition set by Allah Swt. but not just a barrier, but also keeps his people away from something that is dangerous or can harm him that humans may not realize. (3) Solutions to overcome despair by being patient, reading the Qur'an, optimism and doing good deeds